Toleransi Meja Makan: Bisnis, Budaya Pedagang Kuliner, dan Interaksi Sosial Pedagang di Kota Singkawang - Saliro, Sri Sudono; Muchsin, Tamrin; Baharuddin, Baharuddin (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2021)
This study attempted to analyze the relationship between